Motivating tension. Itineraries of ethnic identity in indigenous university students from Peru - Merino Solari, Renatto (2022)
This article is based on the author’s experience as a lecturer in a teacher training program in Intercultural Bilingual Education. It reflects on how the ethnic identity of indigenous young people is constructed before they start their university studies. The aim is to explore the process of identity construction (“Who am I?” “Who are we?”) from significant spaces and experiences in which ethnicity is manifested. This journey attempts to reconstruct the paths followed by young people before entering university as well as the different meanings acquired by their identities. It concludes that assuming oneself as Quechua, Shipibo, Aymara or as a member of any native community constitutes a choice affected by a conflictive intersubjectivity; it is also concluded that ethnic affirmation is a dynamic, conflictive experience in permanent negotiation and without a predefined teleology presented as a motivating tension capable of enabling being and existing.